Hammersmith Infant Neurological Examination in infants born at term: Predicting outcomes other than cerebral palsy. (24th February 2022) - Romeo, Domenico M.; Cowan, Frances M.; Haataja, Leena; Ricci, Daniela; Pede, Elisa; Gallini, Francesca; Cota, Francesco; Brogna, Claudia; Romeo, Mario G.; Vento, Giovanni; Mercuri, Eugenio
Abstract: Aim: We explored the ability of the Hammersmith Infant Neurological Examination (HINE) to identify cognitive performance delay at 2 years in a large cohort of infants born at term. Method: We conducted a retrospective study of infants born at term at risk of neurodevelopmental impairments assessed using the HINE between 3 and 12 months post‐term age and compared them with a cohort of typically developing infants born at term. All infants performed a neurodevelopmental assessment at 2 years of age using the Mental Development Index (MDI) of the Bayley Scales of Infant Development, Second Edition; the presence of cerebral palsy (CP) was also reported. The infants were classified as being cognitively normal/mildly delayed or significantly delayed (MDI < 70). The predictive validity of HINE scores for significantly delayed cognitive performance, in infants with and without CP, was calculated using specific cut‐off scores according to age at assessment. Results: A total of 446 at‐risk and 235 typically developing infants (345 males, 336 females; mean [SD] gestational age 38.7 weeks [1.4], range 37–43 weeks) were included. Of the at‐risk infants, 408 did not have CP at 2 years; 243 had a normal/mild delayed MDI and 165 had an MDI less than 70. Of the at‐risk infants, 38 developed CP. HINE scores showed a good sensitivity and specificity, mainly after 3 months, for identifying significantly delayed cognitive performance in infants without CP. In those with CP, the score was associated with their cognitive performance. The comparison group had the highest HINE scores. Interpretation: The HINE provides evidence about the risk of delayed cognitive performance at age 2 years in infants born at term with and without CP. Abstract : This original article is commented on by Cao and Huang on pages 813‐814 of this issue. RESUMEN: Examen neurológico infantil de Hammersmith en bebés nacidos a término: su uso para predecir otras condiciones además de la parálisis cerebral: Objetivo: Valoramos la capacidad del examen neurológico infantil de Hammersmith (HINE) para identificar el retraso en el rendimiento cognitivo a los 2 años en una cohorte grande de bebés nacidos a término. Método: Realizamos un estudio retrospectivo de bebés nacidos a término con riesgo de trastornos del desarrollo neurológico evaluados mediante el HINE entre los 3 y los 12 meses de edad postérmino y los comparamos con una cohorte de bebés nacidos a término con un desarrollo típico. Todos los bebés realizaron una evaluación del desarrollo neurológico a los 2 años de edad utilizando el Índice de Desarrollo Mental (MDI) de las Escalas de Desarrollo Infantil de Bayley, Segunda Edición; también se informó la presencia de parálisis cerebral (PC). Los bebés se clasificaron como cognitivamente normales/levemente con retreaso o significativamente con retraso (MDI < 70). La validez predictiva de las puntuaciones HINE para el rendimiento cognitivo con retraso significativo, en bebés con y sin parálisis cerebral, se calculó utilizando puntuaciones de corte específicas según la edad en la evaluación. Resultados: Se incluyeron un total de 446 lactantes en riesgo y 235 con desarrollo normal (345 varones, 336 mujeres; edad gestacional media [DE] 38, 7 semanas [1, 4], rango de 37 a 43 semanas). De los lactantes en riesgo, 408 no tenían parálisis cerebral a los 2 años; 243 tenían un MDI con retraso normal/leve y 165 tenían un MDI inferior a 70. De los bebés en riesgo, 38 desarrollaron PC. Las puntuaciones HINE mostraron una buena sensibilidad y especificidad, principalmente después de 3 meses, para identificar un rendimiento cognitivo severo en lactantes sin PC. En aquellos con PC, la puntuación se asoció con su rendimiento cognitivo. El grupo de comparación tuvo las puntuaciones HINE más altas. Interpretación: El HINE proporciona evidencia sobre el riesgo de retraso en el rendimiento cognitivo a los 2 años de edad en bebés nacidos a término con y sin parálisis cerebral.